Profile of pig farms combining high performance and low antimicrobial usage within four European countries. (1st December 2017) - Collineau, Lucie; Backhans, Annette; Dewulf, Jeroen; Emanuelson, Ulf; grosse Beilage, Elisabeth; Lehébel, Anne; Loesken, Svenja; Okholm Nielsen, Elisabeth; Postma, Merel; Sjölund, Marie; Stärk, Katharina D C; Belloc, Catherine
Abstract : Pig farmers are strongly encouraged to reduce their antimicrobial usage because of the rising threat from antimicrobial resistance. However, such efforts should not compromise the herd health status and performance. This study aimed to describe the profile of so‐called 'top‐farms' that managed to combine both high technical performance and low antimicrobial usage. A cross‐sectional study was conducted among 227 farrow‐to‐finish farms in Belgium, France, Germany and Sweden. Among them, 44 farms were allocated to the top‐farms group and were compared with the 'regular' farms group in terms of farm characteristics, biosecurity and health status. Top‐farms had fewer gastrointestinal symptoms in suckling pigs and fewer respiratory symptoms in fatteners, which could partly explain their reduced need for antimicrobials and higher performance. They also had higher biosecurity and were located in sparsely populated pig areas. However, 14 farms of the top‐farms group were located in densely populated pig areas, but still managed to have low usage and high technical performance; they had higher internal biosecurity and more extensive vaccination against respiratory pathogens. These results illustrate that it is possible to control infectious diseases using other approaches than high antimicrobial usage, even in farms with challenging environmental and health conditions.